Pembuatan Ecobrick sebagai Upaya Pengelolaan Limbah Plastik dan Pelestarian Lingkungan di Desa Rejosari Kecamatan Kangkung Kabupaten Kendal - Etin Ekaturrahmi; Lafiah Lafiah; Muhammad Choirul Anwar; Salsabila Safirana Wibisono; Eros Alfedo Hermanto; Rita Ariyana Nur Khasanah (Lembaga Pengembangan Kinerja Dosen, 2024)
Plastic waste is a common problem in all regions of Indonesia. As one of the largest contributors to plastic waste in the world, Indonesia faces a major challenge in plastic waste management. One creative solution that is gaining popularity is ecobricking, an environmentally friendly plastic waste management technique that turns plastic waste into strong and durable “bricks”. This research uses a qualitative method in the process, where data is taken through direct observation in the Rejosari village environment, experiment, as well as literature studies from books, journal articles, and other archives. Through the KKN work program, 84 ecobricks were successfully made by collecting plastic waste from grocery stores, food stalls, and markets. Approximately 7 kg of plastic waste has been absorbed for the needs of ecobricking. Overall, ecobricks have great potential in reducing plastic waste, increasing community awareness of the importance of waste management, as an environmental conservation effort, while supporting local economic empowerment.